Brilliant - Vail, Rachel (HarperTeen, 2010)
Sixteen-year-old Quinn struggles to maintain her image as a brilliant, good girl when her mother's major error at work leads to financial and legal troubles that turn Quinn's and her younger sisters' world upside-down.